Nonprofit fundraising strategy : a guide to ethical decision making and regulation for nonprofit organizations - Pettey, Janice Gow. (Hoboken, NJ : John Wiley & Sons, 2013)
Practical tools and techniques to incorporate ethical standards and practices in nonprofit fundraisingNonprofit Fundraising Strategy features a wealth of practical tools to help fundraising practitioners, board members, and governing boards implement these essential concepts into their own organizations.
About the editor -- Contributing authors -- Foreword / Andrew Watt -- Preface / Robert L. Payton -- Acknowledgments -- Introduction -- Fundraisers and the good life / Paul C. Pribbenow -- The appearance of impropriety / Dianne Lister -- Rights of donors / James M. Greenfield, ACFRE, FAHP -- Public privacy : an Exploration of issues of privacy and fundraising / Eugene A. Scanlan -- Appendix A: ethical codes and standards -- Appendix B: Websites for international fundraising codes of ethics and standards -- Appendix C: Statement of values and standards for excellence of the Tucson Symphony Society dba Tucson Symphony Orchestra.
Includes index.
Includes bibliographical references (at end of each chapter and at pages 435-441) and index.
Print version record and CIP data provided by publisher.
Keywords: Fund raising; Nonprofit organizations -- Finance; Betriebswirtschaft; Fund raising; Nonprofit organizations -- Finance; Electronic books; Electronic books